Simultaneous determination of parabens and inorganic anions in cosmetics by a two-dimensional ultrahigh-performance liquid chromatography-ion chromatography valve-switching method. Issue 52 (27th June 2017) - Wang, Feng-Lian; Zhao, Yong-Gang; Muhammad, Nadeem; Wu, Shu-Chao; Zhu, Yan
Abstract : Simultaneous determination of parabens and inorganic anions in cosmetics in a single injection was obtained in a two-dimensional UHPLC-IC valve switching system. Abstract : A rapid and simple approach involving two-dimensional ultrahigh-performance liquid chromatography (UHPLC) combined with ion chromatography (IC) through valve-switching was developed to determine parabens and inorganic anions in cosmetics simultaneously. Compared with a conventional IC column-switching technique, the proposed method required UHPLC coupled with IC via valve-switching without refreshing the pretreatment column. In this chromatographic system, a mobile phase with 60% methanol and 40% deionized water was used to simultaneously separate parabens, namely, methylparaben (MP), ethylparaben (EP), propylparaben (PP), and butylparaben (BP), and to eliminate the matrix, and KOH eluent (20 mmol L −1 ) was utilized to separate inorganic anions, such as nitrite, sulfite, sulfate, and nitrate. Organic compound analysis, and inorganic anion pretreatment and analysis were simultaneously performed with a single injection. Under optimized conditions, matrix–calibration curves were examined by preparing and analyzing different concentrations of mixture standard solutions containing parabens and inorganic anions. Linearity was between 0.9994 and 0.9999. The limits of detection ranged from 8.0 to 80 μg L −1 . Satisfactory recoveries of cosmetic samples were obtained between 93.9% and 106.2% by adding three representative standard solutions. The proposed method can be applied to routine analysis, as indicated by the validated linearity, accuracy, and precision and potential application on the analysis of MP, EP, PP, BP, nitrite, sulfite, sulfate and nitrate in eight commercial samples.